2013
DOI: 10.1177/1071100713477622
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Brostrom Versus Brostrom-Gould Lateral Ankle Instability Repairs

Abstract: These data suggest that the additional reinforcement of an ankle's lateral ligament complex repair of the ankle with the inferior extensor retinaculum may be marginal at the time of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…After a follow-up of at least 2 years, both groups had the same clinical function. Behrens and collaborators 4 performed the Broström-Gould surgery on 10 fresh cadaveric specimens. Two double-loaded, 3.5-mm-diameter corkscrew suture anchors (Arthrex, Inc, Naples, FL) were used for suture.…”
Section: Discussionmentioning
confidence: 99%
“…After a follow-up of at least 2 years, both groups had the same clinical function. Behrens and collaborators 4 performed the Broström-Gould surgery on 10 fresh cadaveric specimens. Two double-loaded, 3.5-mm-diameter corkscrew suture anchors (Arthrex, Inc, Naples, FL) were used for suture.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical treatment is needed for mechanical lateral ankle instability. Because the residual ATFL ligament in CLAI is still of good quality, and the position of the ligament is superficial, the Broström procedure and modified Broström procedure for suturing extensor retinaculum have become the standard procedures for treatment of CLAI since Broström reported successful treatment of CLAI in 1996 by the direct repair of ATFL. Although the previous reports indicated that use of the Broström procedure of direct repair of ATFL for CLAI has achieved satisfactory clinical results, there was still a 6% to 25% complication rate including ankle pain, ankle swelling, and recurrence of lateral ankle instability.…”
Section: Discussionmentioning
confidence: 99%
“…There is also concern that when using the IER, this is not strictly an anatomical repair since its calcaneal attachment is 10 mm anterior to that of the calcaneofibular ligament (CFL) and this may thus restrict full plantar flexion of the ankle. The need to reinforce lateral ligament repair with the IER is therefore debatable [ 3 ].…”
Section: Introductionmentioning
confidence: 99%